Типология категориально-понятийного аппарата феноменологической социологии (Продолжение) - Шульга, А. (Социология: теория, методы, маркетинг, 2008)
An article is devoted to theoretical problems of phenomenological sociology, and analysis of category-conceptual apparatus of Alfred Schutz as a founder of a new sociological paradigm. The author clarifies theoretical influence of different representatives of philosophy, sociology and psychology on the Schutz’s system, making an emphasis on the role of Edmund Husserl, Max Weber, William James, Herbert Mead. He tries to find out so called “integral category” of the Schutz’s system and to define the central categories, which have four attributive functions, which converts a concept into a category. These functions are: knowledge synthesis function, heuristic function, me tho dological func tion and logical function. The rest concepts, that don’t have these functions, are organized according to the theoretical types. The theoretical system appears as a hierarchical structure, where all categories and concepts take their own places according to their functions and cognitive roles. The first theoretical type is called an “operational” one according to its central category, i.e. the phenomenologically interpreted “social action”. The second type is the “rele vance” one. A “semantic” type is the third one (with “meaning” as its central category). Three last closely connected types are an “epistemic” one (the central category — “stock of knowledge”), an “ontological” one (the central category — “life-world”, “Lebens welt”), and “gnosiological”type. After all, the author sub stan tiates a concept “life world” as an integral category of the phenomenological system of Alfred Schutz.